Impact of Fusobacterium nucleatum on immune cell interactions and gene expression in colorectal cancer: a retrospective cohort study - Heregger, Ronald; Huemer, Florian; Greil, Richard; Canadas-Ortega, Marina; Posselt, Gernot; Ijsselsteijn, Marieke E; Plattner, Christina; Rieder, Dietmar; Trajanoski, Zlatko; Krogsdam, Anne; Klieser, Eckhard; Neureiter, Daniel; et al. (Frontiers in Immunology, 2025)
BackgroundColorectal cancer (CRC) is a major global health concern. The presence of Fusobacterium nucleatum (Fn) in CRC can promote cancer progression by modulating the immune response and creating an immunosuppressive environment.MethodsA cohort of 107 patients with localized CRC treated between 2005 and 2017 was analyzed, categorizing tumors as Fn-positive (Fn+) or Fn-negative (Fn−) using quantitative PCR. Patient characteristics, tumor characteristics and survival data were compared between groups. We further performed bulk RNA sequencing and gene set enrichment analysis to explore differential gene expression between Fn+ and Fn− CRC. Spatial immune cell interactions within the tumor microenvironment were characterized using imaging mass cytometry (IMC) and quantified through Voronoi tessellation-derived mixing scores.ResultsIn 45 out of 107 patients (42%) tumors were classified as Fn+. Fn positivity was significantly associated with poor tumor differentiation (p=0.008) but did not significantly impact overall survival (OS; log-rank p = 0.099) or disease-free survival (DFS, log-rank p=0.595). Fn+ tumors exhibited distinct immunological features: RNA sequencing identified significant downregulation of pathways involved in immune activation and antibacterial defenses. IMC demonstrated increased intratumoral interactions between immune cells, antigen-presenting cells, and tumor cells in Fn+ tumors compared to Fn− tumors, though these differences were not observed at tumor margins. Furthermore, Fn persistence was confirmed in metastatic lesions, suggesting a potential role in tumor spread and disease progression.DiscussionOur findings suggest that Fn contributes to an immunosuppressive microenvironment in CRC, diminishing both antibacterial defense and anti-tumor immunity. Selective elimination of Fn may enhance treatment efficacy and warrants further investigation.